Disease Severity in Moderate-to-Severe COVID-19 Is Associated With Platelet Hyperreactivity and Innate Immune Activation - Jakobs, Kai; Reinshagen, Leander; Puccini, Marianna; Friebel, Julian; Wilde, Anne-Christin Beatrice; Alsheik, Ayman; Rroku, Andi; Landmesser, Ulf; Haghikia, Arash; Kränkel, Nicolle; Rauch-Kröhnert, Ursula (Frontiers in Immunology, 2022)
Background: Hemostasis and inflammation are both dysregulated in patients with moderate-to-severe coronavirus disease 2019 (COVID-19). Yet, both processes can also be disturbed in patients with other respiratory diseases, and the interactions between coagulation, inflammation, and disease severity specific to COVID-19 are still vague. Methods: Hospitalized patients with acute respiratory symptoms and with severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) positive (COVpos) and negative (COVneg) status were included. We assessed adenosine diphosphate (ADP)-, thrombin receptor activator peptide 6 (TRAP)- and arachidonic acid (AA)-induced platelet reactivity by impedance aggregometry as well as leucocyte subtype spectrum and platelet-leucocyte aggregates by flow cytometry and inflammatory cytokines by cytometric bead array. Results: ADP-, TRAP- and AA-induced platelet reactivity was significantly higher in COVpos than in COVneg patients. Disease severity, assessed by sequential organ failure assessment (SOFA) score, was higher in COVpos than in COVneg patients and again higher in deceased COVpos patients than in surviving COVpos. The SOFA score correlated significantly with the mean platelet volume (MPV) and TRAP-induced platelet aggregability. A larger percentage of classical and intermediate monocytes, and of CD4pos T cells (TH) aggregated with platelets in COVpos than in COVneg patients. Interleukin (IL)-1 receptor antagonist (RA) and IL-6 levels were higher in COVpos than in COVneg patients and again higher in deceased COVpos patients than in surviving COVpos. IL-1RA and IL-6 levels correlated with the SOFA score in COVpos, but not in COVneg patients. In both respiratory disease groups, absolute levels of B cell-platelet-aggregates and CD8pos (cytotoxic) T cell-platelet-aggregates were correlated with the relative abundance of that cell type, indicating a universal, but not a COVID-19-specific mechanism. Conclusion: In moderate-to-severe COVID-19, but not in other respiratory diseases, disease severity was associated with platelet hyperreactivity and a typical inflammatory signature. In addition to a severe inflammatory response, platelet hyperreactivity seems to be a relevant contributor to worse clinical outcome in patients with COVID-19, pointing to the importance of antithrombotic therapy for reducing disease severity.